2010
DOI: 10.1111/j.1708-8208.2008.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Mandibular Symphysis Volume as a Source of Bone Grafting

Abstract: AutoCAD did not overestimate the volume of bone that can be safely harvested from the mandibular symphysis. The use of the design software program may improve surgical treatment planning prior to sinus augmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(61 citation statements)
references
References 20 publications
2
56
0
2
Order By: Relevance
“…Unfortunately, in the study by Yamamoto et al, 5 it is not possible to discern the actual course of the inferior alveolar nerve canal and its various sites of contact with the external cortical bone of the ramus and it is in consideration for sagittal split ramus osteotomy, not for bone harvesting from the mandibular ramus. Verdugo et al 8 reported that the mandibular second and third molar areas provided the thickest cortical graft averaging 2.8 6 0.6 mm and that the thinnest bone was immediately posterior to the third molar area (1.9 6 0.3 mm). However, they did not mention the linear distance between the superior aspect of the inferior alveolar nerve canal and the alveolar crest but also the linear distance between the buccal aspect of the inferior alveolar nerve canal and the buccal cortical bone.…”
Section: Discussionmentioning
confidence: 98%
“…Unfortunately, in the study by Yamamoto et al, 5 it is not possible to discern the actual course of the inferior alveolar nerve canal and its various sites of contact with the external cortical bone of the ramus and it is in consideration for sagittal split ramus osteotomy, not for bone harvesting from the mandibular ramus. Verdugo et al 8 reported that the mandibular second and third molar areas provided the thickest cortical graft averaging 2.8 6 0.6 mm and that the thinnest bone was immediately posterior to the third molar area (1.9 6 0.3 mm). However, they did not mention the linear distance between the superior aspect of the inferior alveolar nerve canal and the alveolar crest but also the linear distance between the buccal aspect of the inferior alveolar nerve canal and the buccal cortical bone.…”
Section: Discussionmentioning
confidence: 98%
“…The microstructure is a crucial factor in determining the degree of revascularization. In cancellous bone, the large marrow spaces between the trabeculae allow a better and faster revascularization, while in cortical bone, the high density of bone lamellae impedes blood vessel development, which will be therefore limited to Volkmann's and Haversian canals 13. Although cancellous bone revascularizes earlier and better on one side, it would be more subjected to resorption on the other side in the presence of compressive forces 14…”
Section: Discussionmentioning
confidence: 99%
“…Primarily, the limits of the mental region have been defined by Verdugo et al,12 who evaluated the volume that could be safely harvested from the symphysis region during surgery, to preserve the dental element's vitality superiorly, not to damage the inferior alveolar nerve laterally, and not to compromise the structural resistance of the mandible for preservation of the lingual cortical plate inferiorly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations